ADAPTATION OF ARCHITECTURAL STYLE TO PRESERVE CULTURAL HERITAGE BUILDING Case Study: Vihara Dewi Welas Asih-Cirebon - soewarno, Nurtati (Journal of Architectural Research and Education, 2020)
Abstact – Indonesia is an archipelago that is located between two continents, Asia and Australia, also between two oceans, the Pasific and the Indian ocean. This prospers in the commercial activity. Because of the location, costal cities are more easy to reach, foreigner that drop in have significant impact to these cities, for example Cirebon, a costal city that lies in the north east part of West Jawa. Various foreigners that drop in and also stay in Cirebon could be seen by the heritage, one of them is the Vihara Dewi Welas Asih. The temple as a house of worship for Konghucu religion is easy to be known by the colour and Chinese specific architectural style. The city development pushes to changes, as to the Vihara Dewi Welas Asih, renovation and additional buildings is inevitable. This paper is to study the architectural style applied to the additional buildings surrounding the temple. By observation the architectural style of the new building is recognised, also how the context of the new building compare to the temple. It is expected that the new architectural style will be in harmony with the Vihara Dewi Welas Asih architectural style. It is also expected that intervention by the Local Government in organizing the alteration so the Cultural Heritage area is well maintained, become a tourist destination site giving a positive impact to the continuity of the Cultural Heritage building in Cirebon city. Keywords – architectural style addaptation, Vihara Dewi Welas Asih, Cultural Heritage Building